Chemical Sensor Technologies for Sustainable Development: Recent Advances, Classification, and Environmental Monitoring - Abel Inobeme; Arunadevi Natarajan; Safalmani Pradhan; Charles Oluwaseun Adetunji; Alexander Ikechukwu Ajai; Jonathan Inobeme; Mathew John Tsado; John Olusanya Jacob; Shyam S. Pandey; Kshitij RB Singh; Jay Singh (Advanced Sensor Research)
Abstract One of the significant issues of concern in recent times is detecting, quantifying, and monitoring various chemical contaminants in the environment. Numerous inorganic and organic substances are discharged into the environment from various anthropogenic activities, thereby polluting the ecosystems' air, water, soil, and other components. These contaminants have been documented to have deleterious effects on humans, animals, and the environment. Therefore, the need for monitoring and continual quantification of the contents of these contaminants in various environmental matrices becomes paramount. Many diverse sensors are fabricated for multiple utilizations, including liquids and gas sensors, wireless sensors, electronic tongues, and noses for detecting volatile airborne substances, pollutants, and effluents. This review focuses on cutting‐edge technology used in chemical sensors for environmental protection and sustainable development. It also discusses the fabrication and development of chemical sensors and their working principles. In addition, highlights about the applications of chemical sensors in environmental monitoring are also elaborated. This review article discusses emerging sensor technologies and their application in ecological monitoring. Further, the recognition of chemical warfare agents and homeland security applications with the help of bioelectronic nose and tongue is discussed. Finally, some challenges associated with chemical sensors and future trends are also attempted.